2017
DOI: 10.3390/en10101569
|View full text |Cite
|
Sign up to set email alerts
|

A Stable and Fast-Transient Performance Switched-Mode Power Amplifier for a Power Hardware in the Loop (PHIL) System

Abstract: Power Hardware in the Loop (PHIL) systems are used to test a power system with the help of combined software and hardware. Generally, to construct a PHIL system, a switched-mode power amplifier that has a stable performance is used, because of their large, linear signal control-to-output characteristics. However, the fundamental limitations of a switch-mode power amplifier (PA) are the dynamic performance and output bandwidth. In this paper, a compound controller has been used for the rectifier part of a PA, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The power amplifiers (PA) can be realized using switchedmode amplifiers, linear amplifiers, and generators. Switched mode amplifiers are commonly used for PHIL applications ranging from small-scale up to mega watts range [1], [16], [17]. Linear amplifier has higher bandwidth as compared to switched mode PA.…”
Section: Itm Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…The power amplifiers (PA) can be realized using switchedmode amplifiers, linear amplifiers, and generators. Switched mode amplifiers are commonly used for PHIL applications ranging from small-scale up to mega watts range [1], [16], [17]. Linear amplifier has higher bandwidth as compared to switched mode PA.…”
Section: Itm Interfacementioning
confidence: 99%
“…Figs. 16 shows the PHIL results based on offline simulation for ITM and proposed method when R S = 15 Ω and R L = 10 Ω. The initial conditions setting for the ITM and the proposed method are as follows: For the ITM, I…”
Section: A Case 1: Ls >Llmentioning
confidence: 99%
“…• Linear Amplifier: Furthermore, several research papers of new types of PA for PHIL purposes can be found in [96,98,[109][110][111][112][113]. Usually, these new systems are switched amplifier instead of linear amplifier, due to the fact that it is a more efficient technology and the specific and density power is clearly higher.…”
Section: Power Amplifiermentioning
confidence: 99%
“…In the electrical power sector, applications of HiL for testing and validating are growing. Sun et al [21] used a HiL system to study the dynamic performance of a switch-mode power amplifier. In [22] a power HiL system was introduced and used to evaluate a case study of a Great Britain network.…”
Section: Introductionmentioning
confidence: 99%